At ophæve verdens vægt. Om nostalgi og nærvær hos W.G. Sebald - Baake-Hansen, Martin (Passage - Tidsskrift for litteratur og kritik, 2016)
Martin Baake-Hansen: “Dissolving the Weight of the World. On Nostalgia and Intimacy in W.G. Sebald” This article argues that nostalgia is an important, if often overlooked, aspect in the work of W.G. Sebald. It argues that Svetlana Boym’s concept of reflective nostalgia is key to understanding the way in which The Rings of Saturn (1995) and Austerlitz (2001) meditate on history and memory. Thus, the concept of reflective nostalgia helps us realize that the work of Sebald does not ‘only’ concern melancholy, trauma and the catastrophic history but also contains elements of lightness, intimacy and warm feelings.